Characterization of the Dynamic Thermal Properties of the Opaque Elements Through Experimental and Numerical Tests. (November 2015) - Pernigotto, G.; Prada, A.; Patuzzi, F.; Baratieri, M.; Gasparella, A.
Abstract: The dynamic behaviour of the building opaque elements can be characterized by the periodic thermal transmittance and the time- shift, evaluated according to EN ISO 13786:2007 prescriptions (i.e., under periodic sinusoidal forcing conditions on a side and constant conditions on the other one). A modified hotbox apparatus was built to measure these dynamic parameters. We tested a single-layer timber structure and then we developed and calibrated a numerical model with ANSYS Fluent®. Different boundary conditions have been studied in the numerical model to assess the sensitivity of the results to the boundary conditions, with the aim of refining the experimental procedure.